THE EFFECT OF CONCEPT CIRCLE STRATEGY ON THE STUDENTS’ VOCABULARY ACHIEVEMENT IN READING DESCRIPTIVE TEXTS - Chairunnisa Chairunnisa; Rahmad Husein (Universitas Negeri Medan, 2015)
This study was aimed at finding out the effect of concept circle strategy on the students' vocabulary achievement in reading descriptive text. It was conducted by using experimental research design. The population of this study was the students of SMP Panca Budi Medan, Academic Year 2015/2016. This study was conducted with two randomized groups namely experimental group and control group. The experimental group was taught by using Concept Circle Strategy while the control group was taught by using Frayer Model Strategy. The data was analyzed by using t-test formula. The analysis showed that the mean scores of the students in the experimental group was significantly higher than the mean scores of the students in the control group at the level of significant α= 0.05 with the degree of freedom (df) 50 with t-observed value 3.13> t-table value 2.009. Therefore, null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The findings indicated that using Concept Circle Strategysignificantly affected the students’ vocabulary achievement in reading descriptive text.